A review of amber and copal occurrences in Africa and their paleontological significance - (:unkn) unknown (My University, 2020)
The paleontological interest for fossil plant resins (amber and copal) has greatly increased in thelast decades, as field studies have resulted in the discovery of various new deposits worldwide. Yet, amberrichdeposits remain particularly scarce on continents from former Gondwana. Here we review the knownoccurrences of copal and amber from Africa, with a state-of-the-art regarding the age dating, the putativeplant sources, the fossil content, as well as the paleoenvironmental settings. The first African ambers knownto yield arthropods and other organismal inclusions, found recently from the early Cretaceous of Congo andthe Miocene of Ethiopia, are briefly overviewed.
Keywords: African Research